Unga och sårbara : Om vad Bodens kommun gör för att hjälpa unga brottsutsatta - Hahto, Lina (2012)
Support for young crime victim is an infringed area, and young people are one of the groups in society who face a high risk of falling victim to crime. Many young people do not want to talk about difficulties and for themselves to seek help can be a big step even if they feel in need of both assistance and support. It is therefore essential to clearly state where assistance is available and that society picks up the young people who are in need of support. This paper aims to investigate the possibilities for young crime victims in the municipality of Boden to receive help and support, and to raise the question of developing a support center for young crime victims. Topics to be discussed in this paper are: How does crime exposed children in Boden receive help and support, what is the significance of a support center for young crime victims, how can young people find out where help is available? Statistics from the Crime Prevention Council shows that crime rates in Boden are high for reported crimes such as battery, assault and harassment in relation to the neighboring municipality of Luleå and the whole country. The backbone of this thesis is a qualitative study. The paper shows the importance of collaboration and the importance of outreach work.Keywords: crime victim, youth, support services Validerat; 20120613 (anonymous)